2020
DOI: 10.3390/ijms21197202
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Hearing Loss in C57BL/6J Mice Is Associated with Mitophagy Impairment in the Central Auditory System

Abstract: Aging is associated with functional and morphological changes in the sensory organs, including the auditory system. Mitophagy, a process that regulates the turnover of dysfunctional mitochondria, is impaired with aging. This study aimed to investigate the effect of aging on mitophagy in the central auditory system using an age-related hearing loss mouse model. C57BL/6J mice were divided into the following four groups based on age: 1-, 6-, 12-, and 18-month groups. The hearing ability was evaluated by measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…mRNA levels of BNIP3, PINK1, Parkin and NIX, and the protein levels of BNIP3, PINK1 and Parkin decrease in the mouse auditory cortex with aging [ 197 ];…”
Section: Figurementioning
confidence: 99%
“…mRNA levels of BNIP3, PINK1, Parkin and NIX, and the protein levels of BNIP3, PINK1 and Parkin decrease in the mouse auditory cortex with aging [ 197 ];…”
Section: Figurementioning
confidence: 99%
“…This occurrence may contribute to the cellular changes observed in an old central auditory system, resulting in age-related hearing loss. Thus, NIP3L/NIX may play a vital role in maintaining cochlear cell homeostasis during the aging process of the hearing system [37,38]. BNIP3L was detected at medium levels in all human samples, with strong expression in saccule paralleled by strong expression detected in all mouse cell types.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have found that mitophagy is decreased in ARHL (Oh et al, 2020;Youn et al, 2020). PHB2 has been regarded as the mitophagy receptor (Wei et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…He et al, 2017). However, recent studies have reported that mitophagy was reduced in aged cochlea and central auditory system, which could aggravate cellular damage and increase hearing loss (Oh et al, 2020;Youn et al, 2020). PINK1/Parkin have been identified as important proteins involved in mitophagy.…”
Section: Introductionmentioning
confidence: 99%